Recent progress in steel and composite structures : proceedings of the XIII International Conference on Metal Structures (ICMS2016), Zielona Góra, Poland, 15-17 June 2016 /: proceedings of the XIII International Conference on Metal Structures (ICMS2016), Zielona Góra, Poland, 15-17 June 2016. (2016) - Unknown
No abstract available